Progressive Supranuclear Palsy: A Case Report and Literature Review - Ikram, Samar; Parra-Payano, Valeria D.; Kammaripalle, Thirumala Keerthi Chandrika; Datta, Abhigyan; Kaur, Manpreet; Bhushan, Tanushri; Sullivan, Marlliny; Mastoor, Abeer; Haroon, Humza; Guy, Ali; Rahma, Masum (Archives of Clinical and Medical Case Reports, 2021)
Progressive supranuclear palsy (PSP) is a rare neurodegenerative disease with a prevalence of five to six persons per 100,000 people and characterized by progressive axial rigidity, vertical supranuclear gaze palsy, frontal lobe cognitive decline, and balance issues. The clinical examination findings are diverse and PSP cases are often under-diagnosed or misdiagnosed. We report a case of a 54- year-old male patient that presented primarily with recurrent falls due to postural instability and bilateral leg weakness that had progressively worsened to being wheelchair-bound. An extensive physical examination revealed classical findings indicative of PSP.